Child and Parent Physical Activity, Sleep, and Screen Time During COVID-19 and Associations With Mental Health: Implications for Future Psycho-Cardiological Disease? - Olive, Lisa S.; Sciberras, Emma; Berkowitz, Tomer S.; Hoare, Erin; Telford, Rohan M.; O'Neil, Adrienne; Mikocka-Walus, Antonina; Evans, Subhadra; Hutchinson, Delyse; McGillivray, Jane A.; Berk, Michael; Teague, Sam J.; et al. (Frontiers in Psychiatry, 2022)
The COVID-19 pandemic has afforded the opportunity for some to improve lifestyle behaviours, while for others it has presented key challenges. Adverse changes in global lifestyle behaviours, including physical activity, sleep and screen time can affect proximal mental health and in turn distal cardiovascular outcomes. We investigated differences in physical activity, sleep and screen time in parents and children during early stages of the COVID-19 pandemic in Australia compared to pre-COVID-19 national data; and estimated associations between these movement behaviours with parent and child mental health. Cross-sectional baseline data from the COVID-19 Pandemic Adjustment Study (CPAS; N=2,365) were compared to nationally representative pre-pandemic data from the Longitudinal Study of Australian Children (LSAC; N=9,438). Participants were parents of children aged ≤18 years, residing in Australia. Parents provided self-report measures of mental health, physical activity and sleep quality, and reported on child mental health, physical activity and screen time. Children in CPAS had significantly more sleep problems and more weekend screen time. Their parents had significantly poorer sleep quality, despite increased weekly physical activity. Children’s sleep problems were significantly associated with increased mental health problems, after accounting for socioeconomic status, physical activity and screen time. Poorer parent sleep quality and lower levels of physical activity were significantly associated with poorer mental health. Monitoring this cohort over time will be important to examine whether changes in movement behaviour are enduring or naturally improve with the easing of restrictions; and whether these changes have lasting effects on either parent or child mental health, and in turn, future risk for CVD.